Choroidal Vascularity Index as a Biomarker for Visual Response to Antivascular Endothelial Growth Factor Treatment in Diabetic Macular Edema - Ningxin Dou; Shanshan Yu; Ching-Kit Tsui; Boyu Yang; Jianqiang Lin; Xi Lu; Yue Xu; Benjuan Wu; Jinfeng Zhao; Xiaoling Liang (Journal of Diabetes Research)
Purpose. To investigate the choroidal vascularity index (CVI) as a prognostic factor for the visual efficacy of antivascular endothelial growth factor (VEGF) treatment in diabetic macular edema (DME). Methods. We retrospectively reviewed 92 DME eyes receiving anti-VEGF treatment, which were stratified as responders (≥5 letters gained) and nonresponders (<5 letters gained or lost). Baseline systematic features and optical coherence tomography features, including the CVI, adjusted ellipsoid zone (EZ) reflectivity, subretinal fluid (SRF), and disorganization of the retinal inner layers (DRIL), were evaluated between the two groups. Results. The baseline CVI was significantly lower in nonresponders than in responders (0.66±0.05, 0.69±0.05, and 0.72±0.05, p=0.014). After adjusting for other factors, the baseline CVI, DRIL, SRF, and adjusted EZ reflectivity were significantly associated with visual outcomes (CVI: odds ratio OR=0.17, p=0.006; adjusted EZ reflectivity: OR=0.56, p=0.007; DRIL: OR=6.71, p=0.001; and SRF: OR=0.29, p=0.008). Conclusion. DME patients with a higher CVI, higher adjusted EZ reflectivity, the presence of SRF, and the absence of DRIL at baseline were more likely to gain >5 letters in visual acuity after anti-VEGF treatment. CVI may serve as a novel biomarker for visual response to anti-VEGF treatment in DME.